Utilization of special potential scan programs for cyclic voltammetric development of different nickel oxide-hydroxide species on Ni based electrodes - Pissinis, Diego Ezequiel (2012)
Special potential scan programs were designed for cyclic voltammetric development of β-NiOOH or γ-NiOOH/ β-NiOOH mixtures on the surface of nickel or nickel-chromium (80:20) alloy electrodes in NaOH 0.10 M. The programs consisted on changing the anodic or cathodic switching limit to facilitate the chemical reactions taking place either between Ni(II) hydroxides or between Ni(III) oxides-hydroxides. The electrochemical charge density under the oxidative wave, observed at Ni or Ni-Cr electrode surfaces at approximately 0.48 V (vs SCE), remained almost con- stant with the number of cv cycles after approximately 600 cv cycles at 0.050 V/s. Thus, it can be suggested that a stable proportion of Ni(II)/Ni(III) oxides-hydroxides was obtained on the electrode surfaces. The relative amounts of β-NiOOH or γ-NiOOH species were calculated from the electrochemical charges under their reduction waves in the voltammetric experiments. Higher charge densities were always obtained with Ni-Cr alloy electrodes as compared to pure Ni electrodes. Linear relationships were obtained in our study on the dependence of the oxidative peak current with the square root of the scan rate at a scan rate range between 0.01 V/s and 0.16 V/s.